FANATISME BUTA, HAMBATAN DALAM PROSES MEMBANGUN KOMUNIKASI POSITIF : (TELAAH KRITIS PADA PARA PENDUKUNG CAPRES 2024) - Taufik, Cevi Mochamad; Sila, Gita Eka; Suhaeri (KOMUNIKA BANGSA, 2024)
There was a loud sound of attack on the communication stage. Cynical statements with a tendency to bring down people poured out of the rifles fired by the presidential candidates. The direction is right to break down mental defenses as the last bastion of positive awareness. The attacks were incessant and could no longer be stopped, causing the country to feel like it was in a state of war. The happiness that should have accompanied the presidential election (Pilpres) collapsed into terror narratives communicated by the success team supporting the presidential candidate (capres). Disruptions to positive communication are expressed in content in the form of text, sound and visuals spread across social media networks. Without realizing it, all of this has an influence on hostility among fellow citizens. Based on these conditions, this research aims to determine blind fanaticism with verbal aggression in building positive communication that raises awareness of national identity. To provide a comprehensive explanation, the approach used is qualitative descriptive with critical analysis methods. The results show that the fanatical mentality formed in the presidential election contestation becomes an obstacle in the process of enforcing positive communication. A fanatical mentality triggers hostility because it is based on negative sentiments. Fanaticism can even maintain ongoing grudges because it leaves an impression on the psychological space of the supporters of the presidential and vice presidential candidates. Keywords: Fanaticism, presidential election, positive communication